Recent advances in biotechnology for heparin and heparan sulfate analysis - Qiao, Meng (Talanta, 2020)
Heparan sulfate (HS) is a class of linear, sulfated, anionic polysaccharides, called glycosaminoglycans (GAGs), which present on the mammalian cell surfaces and extracellular matrix. HS GAGs display a wide range of critical biological functions, particularly in cell signaling. HS is composed of repeating units of 1→4 glucosidically linked uronic acid and glucosamine residues. Heparin, a pharmacologically important version of HS, having higher sulfation and a higher content of iduronic acid than HS, is a widely used clinical anticoagulant. However, due to their heterogeneity and complex structure, HS and heparin are very challenging to analyze, limiting biological studies and even resulting in safety concerns in their therapeutic application. Therefore, reliable methods of structural analysis of HS and heparin are critically needed. In addition to the structural analysis of heparin, its concentration in blood needs to be closely monitored to avoid complications such as thrombocytopenia or hemorrhage caused by heparin overdose. This review summarizes the progress in biotechnological approaches in the structural characterization of HS and heparin over the past decade and includes the development of the ultrasensitive approaches for detection and measurement in biological samples.